Eco-friendly water-induced aluminum oxide dielectrics and their application in a hybrid metal oxide/polymer TFT. Issue 105 (13th October 2015) - Liu, Ao; Liu, Guoxia; Zhu, Huihui; Shin, Byoungchul; Fortunato, Elvira; Martins, Rodrigo; Shan, Fukai
Abstract : Eco-friendly water-inducement method was used to fabricate hybrid metal oxide/polymer TFTs based on high- k AlO x dielectric with high electrical performance. Abstract : Solution-processed oxide semiconductors have been widely studied with the objective of achieving high-performance, sustainable and low-cost electronic devices. In this report a simple and eco-friendly water-inducement method has been developed to fabricate high- k dielectrics and hybrid thin-film transistors (TFTs); introducing metal nitrates and deionized water as the precursor materials. The AlO x dielectric films annealed at temperatures higher than 350 °C result in low leakage current densities and the dielectric constants are nearly 7. Instead of the conventional oxide semiconductors, water-induced (WI) polyvinylprrolidone (PVP) was introduced into the In2 O3 solution to form a hybrid metal oxide/polymer channel layer. The 250 °C-annealed WI In2 O3 : PVP TFTs based on AlO x dielectric exhibit outstanding electrical performances and high stability. These promising properties were obtained at an ultra-low operating voltage of 2 V. The WI metal oxide/polymer hybrid TFTs are promising alternatives for applications in low-cost, low-consumption and eco-friendly flexible electronics.